To transfer or not to transfer: Aged care nurses' decision-making in transferring residents to the emergency department. Issue 2 (April 2021) - Gurung, Apil; Sendall, Marguerite Claire; Barnard, Alan
ABSTRACT: Background: Nurses are key decision makers in residential aged care facilities and play a significant role in the transfer of residents from residential aged care facilities to emergency departments. There is scant literature about the role of nurses in the transfer decision-making process. Aim: To describe the experiences of residential aged care facility nurses who engage in decision-making to transfer residents to emergency department. Methods: This research has adopted interpretive qualitative approach of phenomenography. In-depth interviews were undertaken with 20 residential aged care facility nurses across two sites. Uniquely, drawing was used as one way to collect rich, textured data in these in-depth interviews. Findings: Six categories emerged to represent residential aged care facility nurses' conceptions of decision-making about transferring a resident to the emergency department: "Being a marionette"; "Too dumb to have an opinion"; "Making the family happy"; "Not about the resident"; "Having experience"; and "Being on your own". Discussion: Residential aged care facility nurses experienced decision-making as not being able to do what is right for the resident most of the time due to a myriad of factors, with heavy influence of other key stakeholders. Conclusion: Decision-making is described as a professional responsibility wherein residential aged care facility nurses face dilemmas related to the transfer of a resident to the emergency department and perceived as a constraint.